Noble gas composition of Indian carbonatites (Amba Dongar, Siriwasan): Implications on mantle source compositions and late-stage hydrothermal processes - Hopp, Jens; Viladkar, Shrinivas G. (Earth and planetary science letters, 2018)
Within a stepwise crushing study we determined the noble gas composition of several calcite separates, one aegirine and one pyrochlore-aegirine separate of the carbonatite ring dyke complex of Amba Dongar and carbonatite sill complex of Siriwasan, India. Both carbonatites are related to the waning stages of volcanic activity of the Deccan Igneous Province ca. 65 Ma ago. Major observations are a clear radiogenic 4He⁎ and nucleogenic 21Ne⁎ imprint related to in situ production from U and Th in mineral impurities, most likely minute apatite grains, or late incorporation of crustal fluids. However, in first crushing steps of most calcites from Amba Dongar a well-resolvable mantle neon signal is observed, with lowest air-corrected mantle 21Ne/22Ne-compositions equivalent to the Réunion hotspot mantle source. In case of the aegirine separate from Siriwasan we found a neon composition similar to the Loihi hotspot mantle source. This transition from a mantle plume signal in first crushing step to a more nucleogenic signature with progressive crushing indicates the presence of an external (crustal) or in situ nucleogenic component unrelated and superposed to the initial mantle neon component whose composition is best approximated by results of first crushing step(s). This contradicts previous models of a lithospheric mantle source of the carbonatitic magmas from Amba Dongar containing recycled crustal components which base on nucleogenic neon compositions. Instead, the mantle source of both investigated carbonatite complexes is related to a primitive mantle plume source that we tentatively ascribe to the postulated Deccan mantle plume. If, as is commonly suggested, the present location of the Deccan mantle plume source is below Réunion Island, the currently observed more nucleogenic neon isotopic composition of the Réunion hotspot might be obliterated by significant upper mantle contributions. In addition, compared with other carbonatite complexes worldwide a rather significant contribution of atmospheric noble gases is observed. This is documented in cut-off 20Ne/22Ne-ratios of ca. 10.2 (Amba Dongar) and 10.45 (Siriwasan) and cut-off 40Ar/36Ar-ratios of about 1500. This atmospheric component had been added at shallow levels during the emplacement process or later during hydrothermal alteration. However, understanding the late-stage interaction between atmospheric gases and magmatic mantle fluids still requires further investigation.